Subversion of Cell-Autonomous Immunity and Cell Migration by Legionella pneumophila Effectors - Simon, Sylvia; Hilbi, Hubert (Frontiers in Immunology, 2015)
Bacteria trigger host defense and inflammatory processes such as cytokine production, pyroptosis and the chemotactic migration of immune cells towards the source of infection. However, a number of pathogens interfere with these immune functions by producing specific so-called “effector” proteins, which are delivered to host cells via dedicated secretion systems. Air-borne Legionella pneumophila bacteria trigger an acute and potential fatal inflammation in the lung termed Legionnaires’ disease. The opportunistic pathogen L. pneumophila is a natural parasite of free-living amoebae, but also replicates in alveolar macrophages and accidentally infects humans. The bacteria employ the Icm/Dot type IV secretion system and as many as 300 different effector proteins to govern host cell interactions and establish in phagocytes an intracellular replication niche, the Legionella-containing vacuole. Some Icm/Dot-translocated effector proteins target cell autonomous immunity or cell migration, i.e. they interfere with (i) endocytic, secretory or retrograde vesicle trafficking pathways, (ii) organelle or cell motility, (iii) the inflammasome and programmed cell death, or (iv) the transcription factor NF-κB. Here we review recent mechanistic insights into the subversion of cellular immune functions by L. pneumophila.